Lateral Parapatellar Approach with Preservation Infrapatellar Fat Pad in TKA for Severe Valgus Deformity with Flexion Contracture and Patella Subluxation: A Case Report - Darmawan, Dwi Indra; Mulyadi, Dicky (The Hip and Knee Journal, 2024)
Total knee replacement for patients with osteoarthritis and valgus deformity remains challenging, with soft tissue balance often difficult to achieve. Most orthopedic surgeons use the medial parapatellar approach for total knee replacement. However the lateral approach descrbed in this case allows direct acces to the pathology. It is generally very difficult to close the lateral capsular and defect after valgus knee TKA, especially for severe valgus and flexion knee deformity. The creation of laterally based flap is necessary to cover the soft tissue gap resulting on the lateral aspect of the knee after valgus correction. A case report of a secondary osteoarthritis left knee joint with severe valgus deformity, flexion contracture and patella subluxation in a 25-year-old woman is presented. Lateral parapatellar approach total knee arthroplasty was performed with preservation of the infrapatellar fat pad to provides soft tissue covering on the lateral aspect of the knee after valgus correction.